Hypercementosis Associated with ENPP1 Mutations and GACI. (April 2018) - Thumbigere-Math, V.; Alqadi, A.; Chalmers, N.I.; Chavez, M.B.; Chu, E.Y.; Collins, M.T.; Ferreira, C.R.; FitzGerald, K.; Gafni, R.I.; Gahl, W.A.; Hsu, K.S.; Ramnitz, M.S.; et al.
Mineralization of bones and teeth is tightly regulated by levels of extracellular inorganic phosphate (Pi ) and pyrophosphate (PPi ). Three regulators that control pericellular concentrations of Pi and PPi include tissue-nonspecific alkaline phosphatase (TNAP), progressive ankylosis protein (ANK), and ectonucleotide pyrophosphatase/phosphodiesterase 1 (ENPP1). Inactivation of these factors results in mineralization disorders affecting teeth and their supporting structures. This study for the first time analyzed the effect of decreased PPi on dental development in individuals with generalized arterial calcification of infancy (GACI) due to loss-of-function mutations in the ENPP1 gene. Four of the 5 subjects reported a history of infraocclusion, overretained primary teeth, ankylosis, and/or slow orthodontic tooth movement, suggesting altered mineral metabolism contributing to disrupted tooth movement and exfoliation. All subjects had radiographic evidence of unusually protruding cervical root morphology in primary and/or secondary dentitions. High-resolution micro–computed tomography (micro-CT) analyses of extracted primary teeth from 3 GACI subjects revealed 4-fold increased cervical cementum thickness ( P = 0.00007) and a 23% increase in cementum density ( P = 0.009) compared to age-matched healthy control teeth. There were no differences in enamel and dentin densities between GACI and control teeth. Histology revealed dramatically expanded cervical cementum in GACI teeth, including cementocyte-like cells and unusual patterns of cementum resorption and repair. Micro-CT analysis of Enpp1 mutant mouse molars revealed 4-fold increased acellular cementum thickness ( P = 0.002) and 5-fold increased cementum volume ( P = 0.002), with no changes in enamel or dentin. Immunohistochemistry identified elevated ENPP1 expression in cementoblasts of human and mouse control teeth. Collectively, these findings reveal a novel dental phenotype in GACI and identify ENPP1 genetic mutations associated with hypercementosis. The sensitivity of cementum to reduced PPi levels in both human and mouse teeth establishes this as a well-conserved and fundamental biological process directing cementogenesis across species (ClinicalTrials.gov NCT00369421).